COLLABORATION OF ANALYTIC HIERARCHY PROCESS AND SIMPLE ADDITIVE WEIGHTING METHOD TO DETERMINE EMPLOYEE SALARY BONUS - Heribertus Ary Setyadi; Ahmad Fauzi; Galih Setiawan Nurohim (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2022)
Improving the quality of employee performance, a company needs motivation in the form of giving employee bonuses. Bonuses are additional wages given to employees for achieving the best work that has been done in a period. The environmental service of Sragen has implemented a bonus for its employees, however, the bonus has not been assessed based on supporting criteria so that it is not considered objective. This research was made to be able to help determine employee bonuses more objectively by using several criteria that became the basis for giving bonuses. The criteria used are cooperation, behavior, attendance, performance, service and adaptation. The Analytic Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods are used in this study so that the bonus calculation can be more objective. The results of the weights from the AHP will be used as a reference for the calculation of SAW. The decision support system is developed using Java programming. The system created can produce recommendations for the amount of bonuses received by each employee. Keywords: AHP method, SAW method, Employee Salary Bonus Intisari— Dalam meningkatkan kualitas kinerja karyawan suatu perusahaan atau instansi perlu adanya motivasi berupa pemberian bonus karyawan. Bonus upah atau gaji merupakan upah tambahan yang diberikan kepada karyawan atas pencapaian pekerjaan terbaik yang telah dilakukan dalam suatu periode. Dinas Lingkungan Hidup Sragen sudah menerapkan pemberian bonus bagi karyawannya, hanya saja pemberian bonus tersebut belum menggunakan penilaian berdasarkan kriteria-kriteria penunjang sehingga dirasa belum obyektif. Kriteria yang digunakan dalam penelitian ini antara lain kerjasama, perilaku, absensi, kinerja, pelayanan dan adaptasi. Penelitian ini dibuat dengan tujuan untuk dapat membantu menentukan bonus karyawan dengan lebih obyektif yaitu menggunakan beberapa kriteria yang menjadi dasar pemberian bonus. Metode Analytic Hierarchy Process (AHP) dan Simple Additive Weighting (SAW) digunakan dalam penelitian ini agar perhitungan bonus dapat lebih obyektif. Hasil bobot dari AHP akan dijadikan acuan untuk perhitungan SAW. Sistem pendukung keputusan dibuat menggunakan pemrograman Java. Sistem yang dibuat dapat menghasilkan rekomendasi besaran bonus gaji yang diterima masing-masing karyawan. Kata Kunci: metode AHP, metode SAW, bonus karyawan.